Financial stress in the ASEAN-5 economies: Macro-financial vulnerabilities and the role of monetary policy / Tng Boon Hwa - Tng, Boon Hwa (2017)
Using Indonesia, Malaysia, the Philippines, Singapore and Thailand (ASEAN-5) as sample countries, this thesis contributes to the empirical analyses of three gaps in existing literature. The initial analysis addresses a knowledge gap in the measurement of financial stability. Existing measures of financial stability could not simultaneously: (1) reflect stability at a systemic scale; (2) reflect stability with little lag, and (3) incorporate information on the financial structure of the economy. Financial Stress Indices (FSI) are constructed to address these deficiencies. The FSIs are constructed using indicators of stress and weighted using the liability side of the financial structure of the sample economies. The indicators and weights of the FSIs span four major market segments - the equity market, banking system, domestic bond market and foreign finance market. Using data from 1997-2013, the results reveal three periods of higher financial stress. The most severe episode in terms of magnitude and duration was the Asian Financial Crisis (1997- 1998). This is followed by the US technology bubble burst (tech bust) (2000-2001) and the recent Global Financial Crisis (GFC) (2007-2009). Interestingly, higher stress levels were seen during the tech bust compared to the GFC in all countries, except Singapore. The FSIs are subsequently modelled as a panel model to investigate the sources of financial stress in the ASEAN-5 economies. The methodology and model specification extends from the Early Warning System (EWS) literature by: (1) including more external variables to better capture the open-economy aspect; (2) including a measure of regional financial contagion; (3) analysing the entire financial cycle instead of just crisis periods, and; (4) using an instrumental variable approach to address endogeneity concerns. The results show that: US financial stress and regional financial contagion are significant common determinants. For country-specific variables, only bank credit emerged as consistently significant. A positive bank credit gap portends higher financial stress. Analysis of the sources of financial stress within individual markets reveals the importance of the banking system and equity markets for financial stress elsewhere. Country-specific Structural Vector Autoregression (SVAR) models for each ASEAN-5 economy are then estimated to analyse the impact of financial stress on the economy and the relationship between monetary policy and financial stress. The SVAR models are adapted to be suited for small-open economies, by including more external variables and in the model structure, where the external variables affect the domestic variables, but not vice versa. The models incorporate FSIs to reflect financial stress in the global environment and ASEAN-5 economies. The findings show that higher financial stress leads to tighter domestic credit conditions and lower economic activity in all five countries. The impact on the real economy displays an initial rapid decline followed by a gradual dissipation. In Malaysia, the Philippines and Thailand, the central banks reduce policy interest rates (IRs) when financial stress increases, although there is substantial cross-country variation in the magnitude and time dynamics. Lower policy IRs are found to have little significant effects in lowering financial stress, but are still effective in stimulating economic activity through other channels.